Associations between disordered eating, body dissatisfaction, and low energy availability in women collegiate athletes - Le, C. V.; Jagim, A. R.; Jones, M. T.; Fields, J. B. (Journal of the International Society of Sports Nutrition, 2025)
Background Collegiate women athletes face unique challenges regarding nutrition, body image, and athletic performance, which increase their risk for low energy availability (LEA). This risk may be further compounded if there are underlying disordered eating (DE) and body dissatisfaction (BID) behaviors. Therefore, the objective was to examine the prevalence of and relationships between LEA, ED risk and behaviors, and BID among women collegiate athletes from a variety of sports.